Chapter 28: Eggplant Production in Florida - Eric H. Simonne; William M. Stall; Kenneth L. Pernezny; Susan E. Webb; Timothy G. Taylor; Scott A. Smith (EDIS)
This document is HS726, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.